The Role of Job Crafting in Transforming Perceived Overqualification into Meaningful Work: Evidence from Saudi Arabia - Gebril, Haytham; Elgebaly, Hamdy; Elwakeel, Neama; Noureldin, Amr; Aboueldahab, Mohamed; Saleh, ELsayed (Journal of Posthumanism, 2025)
This study examines the relationship between perceived overqualification (POQ) and work meaningfulness, with job crafting as a mediating factor, within the Saudi Arabian workforce. Grounded in Person-Job Fit Theory, the research explores how overqualified employees actively reshape their job roles to enhance their sense of purpose and fulfillment at work. While previous studies have focused on the negative consequences of POQ, this study highlights the role of job crafting as a proactive strategy to mitigate these effects. Using a quantitative, cross-sectional design, data were collected from 480 employees across various industries in Saudi Arabia’s public and private sectors. The results indicate that POQ has a significant positive effect on job crafting, suggesting that overqualified employees engage in job redesign to better align with their skills and career aspirations. Furthermore, job crafting has a strong positive effect on work meaningfulness, reinforcing its importance in enhancing job satisfaction and engagement. However, POQ does not directly influence work meaningfulness, indicating that its impact depends on employees’ ability to engage in job crafting. The study confirms total mediation, demonstrating that job crafting fully explains the relationship between POQ and work meaningfulness. These findings contribute to Person-Job Fit Theory and provide practical implications for organizations to foster job crafting initiatives. Encouraging skill utilization, career adaptability, and leadership support can help overqualified employees maintain engagement and motivation, aligning with Saudi Arabia’s Vision 2030 workforce development goals.